2011
DOI: 10.1007/s10560-011-0238-9
|View full text |Cite
|
Sign up to set email alerts
|

Putting a Human Face on Crimes: A Qualitative Study on Restorative Justice Processes for Youths

Abstract: Restorative justice conferences including Victim Offender Mediation (VOM) are rapidly increasing. Due to a lack of participants' accounts on their experiences, gaining knowledge on how restorative justice works from their perspective is critical, especially to further development of justice policy and practice. In this exploratory qualitative study we interviewed 37 participants in a VOM operating in a mid-sized Midwestern city in the United States. In this article, we examine some youths' experiences in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…Further, through direct communication with victims, when offenders were treated with respect, they reported that they could change their views of victims positively and better understand the impacts of their offences on victims. These findings are congruent with a similar study by Choi et al (2011), who examined experiences of eight young offenders who participated in VOMs in the US. They found that, although young offenders tended to feel that VOM was 'not an easy punishment to take', at the same time they considered it 'a good punishment' because it was an opportunity to: learn the impact of their offences on victims; to see the broader impact of their crimes on people other than victims; to understand victims' perspectives; and to confront victims as real human beings (Choi et al 2011:344).…”
Section: Participants' Viewssupporting
confidence: 90%
See 1 more Smart Citation
“…Further, through direct communication with victims, when offenders were treated with respect, they reported that they could change their views of victims positively and better understand the impacts of their offences on victims. These findings are congruent with a similar study by Choi et al (2011), who examined experiences of eight young offenders who participated in VOMs in the US. They found that, although young offenders tended to feel that VOM was 'not an easy punishment to take', at the same time they considered it 'a good punishment' because it was an opportunity to: learn the impact of their offences on victims; to see the broader impact of their crimes on people other than victims; to understand victims' perspectives; and to confront victims as real human beings (Choi et al 2011:344).…”
Section: Participants' Viewssupporting
confidence: 90%
“…Others have employed qualitative investigations to explore views of participants in RJC (cf Abrams et al 2006;Armstrong 2012;Choi et al 2011;Van Camp and Wemmers 2013). This study follows the latter approach.…”
Section: Introductionmentioning
confidence: 99%
“…When juvenile offenders met their victims through VOM, Choi et al, described four major benefits. Juvenile offenders viewed the VOM as a learning opportunity, an opportunity to see different aspects of their crime, an opportunity to better understand their victim(s), and by placing a human face on their crime, offenders were able to empathize with the victim(s) (Choi et al, 2011). Findings also suggested that empathy often led to remorse, encouraging youth to change their minds and behaviors in a significant way (Choi et al, 2011).…”
Section: Restorative Practicesmentioning
confidence: 99%
“…Juvenile offenders viewed the VOM as a learning opportunity, an opportunity to see different aspects of their crime, an opportunity to better understand their victim(s), and by placing a human face on their crime, offenders were able to empathize with the victim(s) (Choi et al, 2011). Findings also suggested that empathy often led to remorse, encouraging youth to change their minds and behaviors in a significant way (Choi et al, 2011). Albrecht's (2010) research investigated the value of restorative justice for migrant minorities in Finland and Norway.…”
Section: Restorative Practicesmentioning
confidence: 99%
“…Abrams et al (2006) and Eskelinen and Iivari (2005) found that more than half of youth offenders felt nervous in terms of attending and expressing their opinions in RJC. In observations of conferences, Choi et al (2011) similarly found that youth offenders frequently failed to express their emotions, such as remorse, due to their nervousness.…”
Section: Effects Of Limited Developmental and Cognitive Capacities Ofmentioning
confidence: 98%